PENGARUH SARI BUAH NANAS (Ananas comosus) DAN LAMA PENYIMPANAN TERHADAP JUMLAH KOLONI BAKTERI DAN KADAR PROTEIN IKAN BANDENG (Chanos chanos) SEBAGAI SUMBER BELAJAR DALAM PERENCANAAN PEMBELAJARAN BIOLOGI MATERI KINGDOM MONERA - Qorry Aulya Rohmana; Poncojari Wahyono; Samsun Hadi (JPBI (Jurnal Pendidikan Biologi Indonesia), 2015)
PENGARUH SARI BUAH NANAS (Ananas comosus) DAN LAMA PENYIMPANAN TERHADAP JUMLAH KOLONI BAKTERI DAN KADAR PROTEIN IKAN BANDENG (Chanos chanos) SEBAGAI SUMBER BELAJAR DALAM PERENCANAAN PEMBELAJARAN BIOLOGI MATERI KINGDOM MONERA Qorry Aulya Rohmana1, Poncojari Wahyono1, Samsun Hadi1 1Pendidikan Biologi FKIP Universtias Muhammadiyah Malang, e-mail: aulyarohmana16@yahoo.com ABSTRACT The aims of this research is to know effect of any pineaple extract juice concentration and duration of saving and to determine concentration of the pineaple fruit extract juice and duration of saving which are the most optimal to the sum of bacterial colony and protein degree in bandeng fish. Research type used was True Experiment Design. A scheme used was Complete Random Scheme of factorial pattern. Data was as such the total of bacterial colony and protein contained in bandeng fish. Result of the research shows that concentration of pineaple fruit extract juise and duration of saving effect the bacterial colony total and protein containe in bandeng fish. The total of bacterial colony gets more as the duration of saving gets longer. As for protein contained in the bandeng fish gets lower as the saving duration goes. Key Words : Bandeng Fish, Pineaple, Number of Bacterial colony, Rate of Protein